NEGLECTED MONTEGGIA FRACTURE: EXPERIENCE IN ELEVEN PATIENTS: Neglected Monteggia Fracture - Munir, Maj Shahid; Salim, Muhammad; Kayani, Adnan Anwar; Ashraf, Ijaz (Pakistan Armed Forces Medical Journal, 2010)
Objectives: To evaluate surgical options in the treatment of missed monteggia fracture dislocation.Study Design: Case seriesPlace and Duration of the Study: CMH Rawalpindi from May 2007 to August 2009.Patients and Methods: We have presented our surgical experience in 11 patients who reported to CMH Rwp from May 2007 to August 2009. They were treated by close reduction or surgically depending upon the patient age and delay. Boyd’s approach was used for open reduction of the radial head in some cases. Postoperatively they were evaluated by Kim’s elbow performance scoreResults: Patients were all boys. Those below 12 years of age were included in the study. Excellent to good results were observed in those who were treated by open reduction of ulnar fracture by callus trimming with indirect reduction of radial head via interosseous membrane traction.Conclusion: Single forearm bone fracture should be treated as fracture dislocation until proved by adequate radiological survey and clinical examination.